Fatores associados à notificação de acidente de trabalho em unidades sentinela em saúde do trabalhador no município de Fortaleza, Nordeste do Brasil - Lima, Romênia Kelly Soares de (2017)
Among all work-related injuries, Accidents at Work (AT) is considered the most serious. Ignorance of the TA situation, its determinants and its distribution throughout the country makes it impossible to properly analyze the potential factors that originate the TA. OBJECTIVE: To analyze the factors associated with the notification of Work Accidents (AT) in sentinel units in the city of Fortaleza, Northeast Brazil. METHOD: A cross-sectional, analytical study was carried out in five sentinel units for severe and fatal work-related accidents in the city of Fortaleza between February 2013 and June 2014. A total of 354 questionnaires were applied to the professionals responsible for TA reports. The prevalence ratio was used, with a 95% confidence interval and the Pearson chi-square test and / or Fischer's exact test. RESULTS: Of the 354 questionnaires applied, 147 were inadequately completed, being excluded, remaining 207 questionnaires that were analyzed. More than half of the interviewees were female (78.0%), nurses (48.0%) and were in the age range from 31 to 50 years. More than half of those interviewed said they had not participated in any type of training in the area of ​​TA. They present an inefficient knowledge of the laws, policies and ordinances that foment the TA. The time of action in the area, to have participated in at least three courses, to have knowledge about the ordinances and legislation related to the TA, about the SINAN form, to know that TAs are compulsory notification events and to discuss this topic with the work team have been Strongly associated with the chance of reporting (p <0.001). On the other hand, aspects such as gender, age or training time did not show a significant association (p> 0.05). CONCLUSION: Training actions contribute to the sensitization of professionals and improve the quality of TA notifications. It is necessary to strengthen the role of Reference Centers in Occupational Health as an inductor of knowledge, permanent updating and technical support to health services.